Association of anandamide with altered binocular depth inversion illusion in schizophrenia - Reuter, Anne Rebecca; Leweke, F. Markus; Köthe, Dagmar (The world journal of biological psychiatry, 2017)
Objectives: Binocular depth inversion illusion (BDII) represents an illusion of visual perception that involves higher-order visual and cognitive processes. Its impairment has been linked to psychotic conditions and identified as a marker for at-risk mental states. The endogenous cannabinoid system (ECS) is involved in various neurophysiological processes. One of its key components, anandamide, is involved in the pathophysiology of schizophrenia. Little is known about its impact on BDII alterations. Therefore, we explored associations between BDII and anandamide levels.Methods: BDII was conducted and blood and CSF were taken in 28 first-episode antipsychotic-naïve schizophrenia (SZ) patients and 81 healthy controls (HC). Serum and CSF anandamide levels were determined by high-performance liquid chromatography/mass spectrometry.Results: BDII scores were significantly elevated in SZ versus HC, indicating a disruption of illusionary revision of percepts in SZ. Anandamide levels were significantly higher in CSF of SZ compared to HC, while serum anandamide was not. However, we found specific association differences of anandamide levels and BDII scores between schizophrenia patients and controls in serum.Conclusions: These findings support the hypothesis of an involvement of anandamide in cognitive processes impaired in schizophrenia and are consistent with a protective effect of elevated anandamide levels herein.